The SnRK1 kinase: novel regulatory mechanisms and its role in metabolic homeostasis - Peixoto, Bruno Alexandre Teixeira (2021)
"Plant metabolism is tightly controlled to ensure that carbon resources are optimally invested to maximize growth and fitness. One major regulatory system involved in metabolic control is the so-called sucrose-trehalose 6-phosphate (Tre6P) nexus. In this system, Tre6P mirrors sucrose levels and acts as a signal of sucrose availability, regulating its synthesis and consumption to maintain sucrose within optimal levels. This is partly achieved by the diversion of photoassimilates towards organic and amino-acid synthesis when sucrose levels (and in consequence Tre6P) rise, thereby reducing further production of sucrose.(...)"